Regeneration of arsenic spent adsorbents by Fe/MgO nanoparticles. Issue 8 (20th January 2017) - Simeonidis, Konstantinos; Martinez‐Boubeta, Carlos; Rivera-Gil, Pilar; Ashraf, Sumaira; Samaras, Theodoros; Angelakeris, Makis; Tresintsi, Sofia; Mitrakas, Manassis; Parak, Wolfgang J; Monty, Claude; Balcells, Lluis
Abstract: BACKGROUND: Over recent decades, there has been increasing global concern over public health impacts related to water pollution with arsenic. With the development of nanotechnology, nanomaterials are being proposed as alternative agents for water treatment. This study focuses on the use of core‐shell nanoparticles as secondary receptors able to operate under intense conditions and perform efficient yet environmentally friendly regeneration of conventional adsorbents. RESULTS: Hybrid MgO‐coated Fe nanoparticles are proposed, optimized to achieve maximum arsenic uptake under a strong alkaline environment, such as the NaOH stream used to regenerate a typical oxy‐hydroxide adsorption column. The magnetic response of these nanocomposites enables their recovery and recirculation by means of an external magnetic field. A scalable laboratory continuous flow system was designed as a proof‐of‐concept to provide maximum efficiency of the recirculating nanoparticles, as well as complete reuse of the alkaline washing solution. A risk assessment scheme was conducted to evaluate the potential environmental impact of nanoparticle residues by testing the toxicity of arsenic‐loaded materials in RTgill‐W1 cells and their inertization into concrete building blocks. CONCLUSION: The presented methodology illustrates a way to incorporate nanoparticles in water technology taking advantage of their surface activity and magnetic separation potential. © 2016 Society of Chemical Industry